2012
DOI: 10.1584/jpestics.d11-017
|View full text |Cite
|
Sign up to set email alerts
|

Detection of <i>kdr</i> pyrethroid resistance in the cotton aphid, <i>Aphis gossypii</i> (Hemiptera: Aphididae), using a PCR-RFLP assay

Abstract: Two point mutations, Leu1014 to Phe and Met918 to r, located in the domain II region of the para-type voltage gated sodium channel, confer knockdown resistance (kdr) to pyrethroid insecticides in several insect species. PCR ampli cation of this region in a pyrethroid-resistant and pyrethroid-susceptible strain of Aphis gossypii and use of a restriction fragment length polymorphism assay on PCR products (PCR-RFLP) provide the rst direct evidence of the Leu1014 to Phe kdr mutation in a eld isolate of A. gossypii. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 20 publications
2
30
1
Order By: Relevance
“…gossypii was attributed to a target site mutation (L1041F) in the voltage gated sodium channel (Herron et al 2001, Marshall et al 2012 and no super-kdr was observed.…”
Section: Introductionmentioning
confidence: 99%
“…gossypii was attributed to a target site mutation (L1041F) in the voltage gated sodium channel (Herron et al 2001, Marshall et al 2012 and no super-kdr was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Further, knockdown resistance ( kdr ) and/or super‐knockdown resistance ( super‐kdr ) traits that reduce sensitivity to pyrethroids have been shown to be caused by mutations in the insect sodium channel and are responsible for pyrethroid target‐site resistance, which has been recently summarized in excellent reviews by Rinkevich et al ., Dong et al ., and Scott . Briefly, substitution of leucine for phenylalanine at position 1014 (L1014F) in the S6 segment of domain II or substitution of methionine for leucine at position 918 (M918 L) in the linker connecting S4 and S5 in domain II has been reported to be responsible for pyrethroid resistance in A. gossypii . It is noteworthy that only M918 L or L1014F has been detected alone, their co‐occurrence has never been observed in the field population of A. gossypii .…”
Section: Introductionmentioning
confidence: 99%
“…S2). Likewise, there are no SNPs that would confer a change to one of the other known kdr mutations in this position, C, S, H, or W. Given the widespread nature of this particular mutation across taxonomically diverse species, including in the hemipterans Aphis gossypii (Marshall et al ., ), M. persicae (Martinez‐Torres et al ., ), Sitobion avenae (Foster et al ., ), and Triatoma infestans (Fabro et al ., ), this was unexpected. Because there is only 1 codon for methionine, all 7 SNPs known to confer a known pyrethroid‐resistant phenotype to an I, L, T or V are possible (Table ).…”
Section: Resultsmentioning
confidence: 99%